МІЖНАРОДНІ СТАНДАРТИ АДМІНІСТРАТИВНОЇ ЮСТИЦІЇ В УКРАЇНІ - Легка, Оксана Володимирівна (SUPREMANCE OF LAW, 2018)
The article is devoted to the study of international standards, on the basis of which the implementation of the judiciary in the administrative process of Ukraine takes place, as well as the reform of the existing legislation, in order to bring the country to the path of increasing the efficiency of state policy and law.